Latar Belakang Pemilihan Tahuna Sebagai Pusat Ekonomi dan Politik Masa Hindia Belanda - Dwi Kurnia Sandy; Nur Izzatul Ulum (Tumotowa, 2020)
Tahuna is the capital city of The Sangihe Islands Regency within the Tahuna Bay region. This region has been inhabited by various communities as the economic and political center. Since the end of the 19th century, Tahuna has carried out this role. This was inseparable from the placement of representatives of the Dutch Indies Government on Sangihe Besar Island in 1882. The existence of the Dutch Indies Government was inseparable from the high demand for copra on the world market. Therefore, the Dutch East Indies government is looking for regions capable of boosting the need for copra exports. One such area is Sangihe Besar Island. Tahuna's role in the copra trade was as the center for the distribution of copra to Manado. To find out the reason for choosing the year, this paper uses spatial analysis and analysis of the physical environment. Both data from the analysis results are then combined with the fiber to be interpreted to get the factors considered in the choice of location. The results showed that there were three factors behind the election of Tahuna, namely economic factors related to copra trade, geographical factors related to the location of ports and political factors related to the formation of a government hierarchy and the location of settlement locations.